2017
DOI: 10.1007/s00394-017-1482-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with prebiotics, probiotics and synbiotics attenuated cardiac dysfunction by improving cardiac mitochondrial dysfunction in male obese insulin-resistant rats

Abstract: Prebiotics, probiotics, and synbiotics shared similar efficacy in reducing insulin resistance and LV dysfunction in obese insulin-resistant rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 59 publications
7
35
1
Order By: Relevance
“…These data are in line with data produced previously (Zaitone and Essawy, 2012; Tunapong et al, 2018). In agreement, human studies highlighted a causal relationship between excessive caloric intake, weight gain, and tissue resistance to insulin (Delgado et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…These data are in line with data produced previously (Zaitone and Essawy, 2012; Tunapong et al, 2018). In agreement, human studies highlighted a causal relationship between excessive caloric intake, weight gain, and tissue resistance to insulin (Delgado et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies have shown that 12 weeks of HFD consumption caused obese‐insulin resistance in rats . In addition, the HFD consumption is associated with cardiac autonomic imbalance, an increased blood pressure, leading to LV dysfunction . Similar to the HFD, there are studies reported that HFHS also caused obese‐insulin resistance and LV dysfunction, but it did not affect blood pressure in rodents …”
Section: Introductionmentioning
confidence: 98%
“…Both red and green fluorescence intensity were measured by a fluorescence microplate reader (BioTek). Therefore, a decreased red/green fluorescent intensity ratio indicates mitochondrial membrane depolarization [18]. …”
Section: Methodsmentioning
confidence: 99%
“…They were then exposed to an enhanced chemiluminescent substrate (Clarity Western ECL Substrate; Bio-Rad). The Western blot images and densitometric analysis were carried out using the ChemiDoc Imaging system with Image Lab software (Bio-Rad) [16, 18]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation